When body positivity falls flat: Divergent effects of body acceptance messages that support vs. undermine basic psychological needs. (June 2022) - Legault, Lisa; Sago, Anise
Highlights: Uses self-determination theory to create and test different pro-body messages. Shows that need supportive messages increase self-esteem and reduce body shame. In contrast, controlling pro-body messages are not beneficial to body image. Provides novel evidence that the framing of body positive messaging is important. Provides novel empirical foundation for the improvement of pro-body communication. Abstract: Although women now have access to messaging about body acceptance, the risks and benefits of such messaging are not well-researched. Using a self-determination theory framework, we contrasted need-supportive versus need-undermining messages about body acceptance. One message supported the basic psychological need for autonomy (i.e., personal agency to accept one's body); one targeted the basic need for body acceptance from others; and one used pressure to elicit body positivity – a need-undermining strategy. We contrasted these messages with one another and with a typical message of thinness idealization. In Experiments 1–4, we found that pressuring pro-body messages were more harmful to body image than messages that used autonomy support and acceptance from others. That is, they produced more pressure, less agency, and lower acceptance. Moreover, Experiments 2–4 showed that need-supportive messages increased state self-esteem from baseline, whereas pressuring body positivity did not. In Experiment 3 message-related self-perceptions mediated the effect of need-supportive messages on state self-esteem. In Experiment 4, need-supportive body acceptance messages reduced body shame and body surveillance, whereas pressure to be body positive did not – and this effect was mediated by body satisfaction induced by the message. We highlight the important difference between need-supportive and need-undermining body positivity.